Analysis of the Relationship between Maternal Knowledge on Early Stimulation and Motor Development in Children Aged 0–24 Months - Yanti, Dian Anggri (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Motor development in early childhood serves as a fundamental basis for supporting a child’s future physical, cognitive, and social growth. Parents—particularly mothers—play a pivotal role in providing appropriate early stimulation. However, limited maternal knowledge often contributes to delays in children’s motor development. This study aimed to identify the relationship between mothers’ knowledge levels and motor development among children aged 0–24 months in the working area of Pagar Jati Health Center.A quantitative observational approach with a cross-sectional design was employed. The study population consisted of 85 mothers with children aged 0–24 months, from which 30 respondents were selected using purposive sampling. Primary data were collected through structured questionnaires assessing maternal knowledge, while secondary data were obtained from medical records and child motor development reports. Data analysis included descriptive and bivariate analysis using the Chi-square test at a 0.05 significance level.The findings showed that 46.7% of mothers had good knowledge, 33.3% had moderate knowledge, and 20.0% had poor knowledge. Most children (66.7%) demonstrated age-appropriate motor development, while 20.0% were classified as doubtful, and 13.3% exhibited developmental deviations. The Chi-square test revealed a significant association between maternal knowledge and children’s motor development (p = 0.031). It can be concluded that higher maternal knowledge is positively associated with a greater likelihood of achieving age-appropriate motor development. These findings highlight the importance of strengthening maternal health education programs to prevent developmental delays in early childhood.